ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI PADA BENGKEL LAS SABAR SUBUR - Tira Dewi Budi Maharani; Tuti Fitriani; Ludia Panggalo (JURNAL ULET (Utility, Earning and Tax), 2025)
This study aims to analyze the cost of production of window trellises, push fences, safety doors, canopies, turnstiles, and stair railings based on the full costing method and calculate the level of profit obtained for each product at Bengekel Las Sabar Subur. This research is a descriptive research. The data collection techniques in this study are observation, interview, and documentation techniques. The data analysis instrument in this study uses the full cost setting method to calculate production costs and the pricing method to determine the profit level. The results of this study show that the cost of production is Rp 288,930 for window trellises, for reinforcing fence products for Rp 3,973,076, for safety door products for Rp 1,245,408, for canopy products for Rp 6,386,958, for turnstile products for Rp 8,136,286, and for stair railing products for Rp 2,749,930. The profit rate of the product is 56% window trellis, 65% push fence, 16% safety doors, 6% canopy, 4% swivel stairs, and 3% stair railings.